2012
DOI: 10.1186/ar3828
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role and mechanism of macrophage migration inhibitory factor in steroid-resistant patients with systemic lupus erythematosus

Abstract: IntroductionGlucocorticoid (GC) therapy remains important in improving the prognosis of patients with systemic lupus erythematosus (SLE). However, some patients do not achieve an effective response with GC treatment, creating an obstacle to the remission of SLE. Identification of the underlying mechanisms responsible for steroid resistance can be significant. Macrophage migration inhibitory factor (MIF) arouses our interest because of its reciprocal relationship with GCs. In the present study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 34 publications
(41 reference statements)
2
39
0
Order By: Relevance
“…Therefore, the discovery of glucocorticoid congeners that preserve the immunosuppressive but not the stimulatory activity of MIF will be useful as a novel and more efficient approach for the treatment of inflammatory diseases [Leng et al, 2009]. The correlation between increased MIF level, MIF gene polymorphism and steroid resistance has been reported in several autoimmune diseases and in human CEM (isolated from continuous culture of human lymphoblasts) T-cell lines [Wang et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the discovery of glucocorticoid congeners that preserve the immunosuppressive but not the stimulatory activity of MIF will be useful as a novel and more efficient approach for the treatment of inflammatory diseases [Leng et al, 2009]. The correlation between increased MIF level, MIF gene polymorphism and steroid resistance has been reported in several autoimmune diseases and in human CEM (isolated from continuous culture of human lymphoblasts) T-cell lines [Wang et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…In the T-lymphoblast cell line, it has been observed that the presence of the mutant C allele creates an AP-4 transcription factor binding site, resulting in a significantly increased MIF expression. It has also been reported that increased MIF concentration was associated with more severe clinical presentations and subsequently a poor outcome of the disease [Renner et al, 2005;Arikan et al, 2006;Wang et al, 2012;Bucala, 2013;Yazdani et al, 2013]. In contrast to other proinflammatory cytokines that are generally suppressed by glucocorticoids, MIF has a very specific counterregulatory effect on glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, accumulating data support that although RIPK1 and RIPK3 kinases first emerged as mediators of necroptosis, they also promote caspase-8-dependent apoptosis and proinflammatory gene expression [12-14]. RIPK1 and RIPK3 promote at least three distinct responses: necroptosis, apoptosis, and cell death-independent inflammation, and the loss of homeostasis of any of these pathways may contribute to the development of pathology [12, 15, 16]. Therefore, the aim of this study is to determine RIPK1 expression and investigate whether RIPK1 contributes to NETs formation in SLE patients.…”
Section: Introductionmentioning
confidence: 99%